Brucella melitensis Wzm/Wzt System: Changes in the Bacterial Envelope Lead to Improved Rev1Δwzm Vaccine Properties - Mena-Bueno, Sara; Poveda-Urkixo, Irati; Irazoki, Oihane; Palacios, Leyre; Cava, Felipe; Zabalza-Baranguá, Ana; Grilló, María Jesús (Frontiers in Microbiology, 2022)
The lipopolysaccharide (LPS) O-polysaccharide (O-PS) is the main virulence factor in Brucella. After synthesis in the cytoplasmic membrane, O-PS is exported to the periplasm by the Wzm/Wzt system, where it is assembled into a LPS. This translocation also engages a bactoprenol carrier required for further biosynthesis pathways, such as cell wall biogenesis. Targeting O-PS export by blockage holds great potential for vaccine development, but little is known about the biological implications of each Wzm/Wzt moiety. To improve this knowledge and elucidate its potential application as a vaccine, we constructed and studied wzm/wzt single- and double-deletion mutants, using the attenuated strain B. melitensis Rev1 as the parental strain, allowing us to describe the composition of Brucella peptidoglycan for the first time. We observed that these mutants lack external O-PS but also trigger changes in genetic transcription and in phenotypic properties associated with the outer membrane and cell wall. Both mutants are highly attenuated; unexpectedly, Rev1wzm also excels as an immunogenic and effective vaccine against B. melitensis and B. ovis in mice, revealing that low persistence is not at odds with efficacy. Rev1∆wzm is attenuated in BeWo trophoblasts, does not infect mouse placentas, and is safe in pregnant ewes. Overall, these attributes and the minimal serological interference induced in sheep, makes Rev1∆wzm a highly promising vaccine candidate.